Basketball footwear requirements are dependent on playing position - Brauner, T.; Zwinzscher, M.; Sterzing, T. (Footwear Science, 2012)
ntroduction: Basketball contains numerous types of movements and highly specific playing positions, and hence the anthropometric profile of players varies considerably. To date, the subjective demands of basketball footwear have not been investigated in depth, either biomechanically or from the players` perspective. This study aimed to investigate players` subjective demands of basketball footwear according to playing position and respective physical game requirements.